Development and validation of a Good Governance Practices (GGP) scale of student leaders - Mutya, Romel C. (Masyarakat, Kebudayaan dan Politik, 2025)
Good governance is becoming an increasingly important component of public institutions; however, the instruments used to assess good governance practices among student leaders are inadequate, resulting in a gap in assessing and improving leadership. This study aims to produce an assessment instrument that can identify and measure the good governance practices (GGP) of prospective student leaders. The method used is a quantitative research design with 349 survey responses from student leaders at higher learning institutions in the Philippines. The Good Governance Practices scale for student leaders comprises 20 items distributed across five dimensions—accountability (3), effectiveness and efficiency (6), participation (5), rule of law (3), and transparency (3)—and shows strong factor loadings (0.710–0.907). The scale exhibited good reliability and model fit, as indicated by χ²/df = 2.444, RMSEA = 0.054, SRMR = 0.038, and CFI = 0.948. Composite reliability values ranged from 0.780 to 0.904, while Cronbach’s alpha coefficients varied between 0.793 and 0.902, confirming strong internal consistency. Results report a psychometrically sound instrument to measure good governance practices of student leaders. This study concludes that the resulting instrument can educate leadership and inform policymaking to establish quality student governance.